The Use of AI Counselling to Enhance Self-Esteem in the Job Seeking Process for Chinese Undergraduate Students - Petsangsri, Sirirat; Zhou, Kangkang; Sriwisathiyakun, Kanyarat (My University, 2024)
Purpose: This study aimed to find the effectiveness of using AI career counseling platform comprising career guidance, entrepreneurship guidance, Job-seeking guidance and alumni networks to enhance Chinese undergraduate students’ self-esteem in the job seeking process. Methods: One-group pretest-posttest experimental design was utilized in this study, with a group of 60 undergraduate students, selected by purposive sampling method to participate in experiment. Furthermore, dependent t test was used to analyze the obtained data. Results: The result showed that there was a significant difference between pretest and posttest of students’ self-esteem with P value as 0.00, the means score of satisfaction towards AI career counseling platform ranged from 4.35 to 4.58. Implications for research and practice: This study demonstrated that the AI career counseling platform is effective to enhance students’ self-esteem. In addition, the study also showed that students were very satisfied with using AI career counseling platform. Consequently, it is recommended that the AI career counselling platform be sustained and further developed to enhance undergraduate students’ self-esteem in the process of job seeking.
Keywords: Artificial Intelligence (AI); Career Counseling platform; Job Seeking; Satisfaction; Self-Esteem